2018
DOI: 10.1097/ta.0000000000001974
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a CT scan practice guideline for pediatric trauma patients reduces unnecessary scans without impacting outcomes

Abstract: Therapeutic study, level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…Among studies targeting several imaging modalities or diagnoses, 74–79% of the studies showed a reduction in use of low-value imaging. In contrast, studies targeting one specific modality only showed that targeting X-ray [ 37 , 47 , 48 , 63 , 64 , 83 , 86 , 90 , 92 , 98 , 104 , 112 , 119 , 124 , 130 ], CT [ 41 , 46 , 49 , 53 , 54 , 58 , 60 , 62 , 67 , 69 , 70 , 77 , 79 , 82 , 87 , 88 , 94 96 , 101 , 102 , 106 , 108 , 121 123 , 125 127 , 129 ] or MRI [ 45 , 68 , 75 , 105 , 118 ] led to a 87, 86, and 83% reduction in low-value imaging, respectively. Few studies included other imaging modalities.…”
Section: Resultsmentioning
confidence: 99%
“…Among studies targeting several imaging modalities or diagnoses, 74–79% of the studies showed a reduction in use of low-value imaging. In contrast, studies targeting one specific modality only showed that targeting X-ray [ 37 , 47 , 48 , 63 , 64 , 83 , 86 , 90 , 92 , 98 , 104 , 112 , 119 , 124 , 130 ], CT [ 41 , 46 , 49 , 53 , 54 , 58 , 60 , 62 , 67 , 69 , 70 , 77 , 79 , 82 , 87 , 88 , 94 96 , 101 , 102 , 106 , 108 , 121 123 , 125 127 , 129 ] or MRI [ 45 , 68 , 75 , 105 , 118 ] led to a 87, 86, and 83% reduction in low-value imaging, respectively. Few studies included other imaging modalities.…”
Section: Resultsmentioning
confidence: 99%
“…The topic of CT efficacy for the evaluation of injuries in trauma patients is highly debated in the literature [3,[6][7][8][17][18][19]. Although several efforts have previously been made to implement judicious use of diagnostic algorithms and CT imaging in emergency and trauma settings [18][19][20][21][22][23], indiscriminate CT imaging as a screening measure, especially for low impact injuries, may pose a challenge for already strained healthcare infrastructures [17,[24][25]. Uniform CT scans in trauma patients with normal vitals may delay diagnosis and treatment for other patients with non-traumatic but serious illnesses.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional abdominal ultrasound is considered the best choice for the follow-up of these patients, although there is no consensus about the time and impact on the evolution. On the other hand, some series report the absence of complications in the follow-up of these patients, reaching figures of up to 87% without requiring radiological studies, regardless of the degree of injury [11,12,15,16].…”
Section: Discussionmentioning
confidence: 99%